APPLICATION OF ARTIFICIAL INTELLIGENCE (AI) FOR HIJAB BUSINESS IN MOJOKERTO USING SENTIMENT ANALYSIS METHOD NATURAL LANGUAGE PROCESSING (NLP) - Fahrur Rijal Ardiyanto; Yuni Rosita Dewi; Zenita Afifah Fitriyani; Oktaviani Permatasari (Jurnal Ekonomi, 2023)
Artificial Intelligence (AI) is an activity aimed at making machines intelligent. AI has been applied in various fields in the 4.0 digital era, including business and industry. As a country with Muslim majority, the hijab business is a promising business. The development of promotional aspects is also diverse, begin from manual promotions using brochures to the using social media and e-commerce marketing. AI can also be used to find out which hijab products are most in demand using the sentiment analysis method. Sentiment analysis data is obtained from reviews or comments of buyers or users of hijab products. Of course, the data form is text data. To process text data, grouping or labeling the comments into positive and negative comments. Then, the labeled data set is processed using machine learning that special for sentiment analysis, namely Natural Language Processing (NLP). NLP is a field of computer science which is a branch of artificial intelligence and language (linguistics) that deals with interactions between computers and human natural language. The hijab brand sample taken from social media is a brand that has been verified as an official brand. For example, Elzatta, Rabbani, and Zoya. The social media used as the data source comes from Instagram and the e-commerce is taken from Shopee. The accuracy of the NLP model is 96% with two classes, namely positive sentiment and negative sentiment. The results obtained can be recommended to hijab business entrepreneurs in Mojokerto City. The benefits of this research can be felt by entrepreneurs to determine the hijab brand that is most in demand by residents of Mojokerto City.